Pre-extension Demonstration and Evaluation of Improved Food Barley Varieties in Chora and Gechi Districts of Buno Bedele Zone Southwestern Oromia, Ethiopia - Suleiman Aman; Nuru Temam; Diriba Hordofa (International Journal on Food, Agriculture and Natural Resources, 2024)
The experiment was conducted in 2022 main rainy cropping season in Chora and Gechi districts of Buno Bedele zone with the objectives to evaluate the yield performance and economic profitability of food barley varieties, to identify farmers’ varietal selection criteria and to improve the targeted farmers` knowledge and skills towards improved selected food barley production and management practices. Based on barley production potential and road accessibility, five kebeles were selected where two improved barley varieties (Adoshe and HB 1307) were demonstrated and evaluated alongside the local variety (Torja) replicated on 14 demonstration sites. The 100 m2 plot size was used for each variety where all the recommended agronomic practices were followed. Data like grain yield, farmers’ varietal selection criteria’s, number of training and field day participants, cost incurred and profit obtained were collected where descriptive statistics, one way ANOVA, matrix raking and partial budget were used to analyze the collected data. Both list-wise deletion and single imputation methods were used in order to fix non-equal treatment as missed data among the fourteen demonstration sites. Accordingly, the descriptive result of list-wise deletion revealed that, the mean grain yield of 37.14, 39.79and 19.49 qt ha-1 were obtained from Adoshe, HB1307 and local varieties respectively whereas the mean grain yield of 34.04, 39.79 and 19.69 qt ha-1 were obtained from Adoshe, HB1307 and local varieties respectively. The list-wise deletion and imputation method analysis of variance among the yield of demonstrated barley varieties shows that there is statistically significant yield difference at (P<0.05) and (P<0.01) between the varieties respectively. The matrix raking shows Adoshe variety was preferred first by farmers. About 69 and 96 participants were participated on the training and field day respectively. The economic analysis result revealed that, the 3.55 ETB marginal rate of return by list-wise deletion and 3.51 ETB by imputation methods were obtained from HB1307 variety whereas, the 3.1 ETB marginal rate of return by list-wise deletion and 2.51 ETB by imputation methods were obtained from Adoshe variety indicating that farmers can recover all the incurred costs and gain 3.55/3.51 and 3.10/2.51 ETB for every 1 ETB they invest when they use HB1307 and Adoshe varieties respectively. HB1307 variety had high performance in terms of yield and economic profitability whereas Adoshe variety was favored by the farmers and therefore, HB1307 and Adoshe varieties were recommended for further scaling up in the study areas and similar agro ecologies.Key words__ Buno Bedele, Demonstration, Farmers, Food Barley, Participatory, Yield.